Seed Inoculation of Rhizobium sp. and Plant Growth Promoting Rhizobacteria in Mungbean Influenced the Dynamics of Mineral N in Soil during Succeeding Wheat - Neha; Ramesh Chandra (Journal of the Indian Society of Soil Science, 2026)
of nitrogen fixing and returning carbon input in soil. Inoculation of legumes with Rhizobium sp. and plant growth promoting rhizobacteria (PGPR) is recommended for improving biological nitrogen fixation (BNF), yields and enhancing soil fertility. This study aimed to examine the effect of microbial inoculation in mungbean on yields and mineral N release behavior during succeeding wheat in a field study conducted for 2 years in a sandy loam soil of terai region, Pantnagar, Udham Singh Nagar, Uttarakhand, India. Microbial inoculation treatments in mungbean consisted of individual and conjoint use of Rhizobium sp. and PGPR and an uninoculated control. The succeeding wheat crop was raised with 3 N levels of 50, 75 and 100% recommended dose of fertilizers (RDF). Results revealed that mineral nitrogen (NH4 +–N + NO3 ––N) and NH4 +–N in the soil decreased with increasing crop age under all the treatments, however, NO3 ––N in soil increased with crop age. The reduction in soil mineral N at different intervals varied with different treatments, being minimum under Rhizobium sp.+ PGPR and maximum under RDF at 148 days. This treatment was followed by Rhizobium in reduction of soil mineral N content. The mineral N content increased due to combined inoculation of Rhizobium sp. + PGPR by 41.3, 46.1, 62.9, 67.3 and 72.5% higher than no inoculation and 14.8, 16.8, 21.3, 23.7 and 26.3% than PGPR alone inoculation treatments at 28, 58, 88, 118 and 148 days after sowing (DAS), respectively. NH4 +–N content in soil also indicated similar pattern registering maximum content with Rhizobium sp. + PGPR and minimum with uninoculated control at similar observational intervals. The NO3 ––N in soil increased with crop age. Treatment of Rhizobium sp. alone and Rhizobium sp. + PGPR were statistically comparable and recorded significantly more NO3 ––N in soil than the uninoculated control, PGPR alone and RDF treatments. It could be concluded that application of diazotrophic bacteria Rhizobium sp., alone or in combination with PGPR in preceding mungbean crop had positive impact on soil mineral N content and grain yields of succeeding wheat, irrespective of fertilizer N levels.